Update on Dementia 2016
DOI: 10.5772/64562
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Visual Cortex in Healthy Aging and Dementia

Abstract: This chapter reviews the differences in specific structural and functional characteristics of human visual cortex among young adults, healthy aging adults, and patients with dementia, with a primary focus on those with Alzheimer's disease (AD). Such visual cortex changes have been shown to underlie many of the behavioral deficits that develop in healthy aging and AD. Measurements of disordered visual cortex in dementia patients may be possible early in the course of neurodegeneration and thus may be useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 156 publications
(359 reference statements)
0
14
0
Order By: Relevance
“…The increase in nonspecific errors in the tritan and deutan axes observed in our AD patients suggests that, in addition to the loss of magno- and parvocellular-cells mentioned above, the koniocellular pathway could also be involved due to its association with the blue-yellow spectrum [51]. In addition, it has also been described that patients with AD have a significant reduction in the V4 area, which is a key region that processes colour vision [52,53]. On the other hand, degeneration in the photoreceptor layer has also been described in patients with AD, which is not restricted to a single cone type due to the decrease in melatonin and its antioxidant effects that occur in this pathology [54,55].…”
Section: Discussionmentioning
confidence: 85%
“…The increase in nonspecific errors in the tritan and deutan axes observed in our AD patients suggests that, in addition to the loss of magno- and parvocellular-cells mentioned above, the koniocellular pathway could also be involved due to its association with the blue-yellow spectrum [51]. In addition, it has also been described that patients with AD have a significant reduction in the V4 area, which is a key region that processes colour vision [52,53]. On the other hand, degeneration in the photoreceptor layer has also been described in patients with AD, which is not restricted to a single cone type due to the decrease in melatonin and its antioxidant effects that occur in this pathology [54,55].…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that neuronal death during normal aging is significantly less as compared to the high cell loss in AD [84]. AD, the most common form of dementia, has been characterized as a progressive neurodegenerative disease that selectively damages neural circuits, and it is distinguished by neurite dystrophy present in about 80% of the aged population having dementia [5,84,103,104]. Age-dependent loss of neurons, decline in synaptic plasticity, and cognitive impairments are often observed in normal aging and neurodegenerative diseases such as AD [84,105,106].…”
Section: Circuit Mechanisms For Normal and Diseased Aging Of Visual Fmentioning
confidence: 99%
“…A great amount of research over the past few decades has shown the dynamic nature of neuroanatomical and functional organization of neural circuits in human, non-human primates, and other species that alter in response to various stimuli [17,39]. Neuroimaging studies have shown lower levels of blood oxygen level dependent (BOLD) activity in V1 of elderly subjects as compared to young adults, while no significant effect on fixation stability was observed in aged adults, which is an important parameter used for visual field map assessments [5,103]. Previous studies discussing various modeling methods of the population receptive field have demonstrated several alterations such as decreased foveal surface area and increased RF sizes in the V1 of elderly subjects as compared to young adults [5,103].…”
Section: Circuit Mechanisms For Normal and Diseased Aging Of Visual Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of individual AFMs along the cortical hierarchy will help reveal the distinct stages of top-down and bottom-up auditory processing. In addition, changes in AFMs can be tracked to study how auditory cortex changes under various attentional and working memory tasks and disorders (e.g., [145,[171][172][173][174][175][176][177]).…”
Section: Measuring Attention and Working Memory In Human Afmsmentioning
confidence: 99%